A Communication Complex Approach to Autism Awareness Training Within First Response Systems in Indiana - Rascon, Natasha A. (Frontiers in Communication, 2022)
Providing Autism and communication training to facilitate better interactions in emergency situations between first responders and individuals with Autism is a critical need. Although trainings exist for first responders, “typical training already being provided on the job is not sufficient” (IBCCES). In addition, while resources—such as YouTube videos—are available, the process for viewing, discussing, and debriefing over the material along with the development of more effective conversational practices is an unexplored space. This case study describes the use of the Communication Complex (CC) perspective for training Volunteer Firefighters in Indiana, emphasizing the development of knowledge and skills necessary for effectively managing this often challenging context. It extends the body of CC research that relates to first responders and other health care providers (e.g. Deason, 2020; Parrish-Sprowl, 2015b; Parrish-Sprowl et al., 2020, Parrish-Sprowl & Parrish-Sprowl, 2014, 2020). An elaboration of the theoretical framing is provided, followed by a brief introduction to Autism and a discussion of safety concerns in the community. Finally, a detailed analysis of the case study is presented. Reports from the participants indicate that Autism awareness training through a CC approach can enable more desirable interaction patterns in emergency situations involving first responders and those with Autism. The findings suggest that the CC approach is effective for enhancing understanding, which can positively impact future scenarios involving individuals with Autism and their families and increase feelings of safety.